Alanine Dehydrogenase Activity Is Required for Adequate Progression of Phycobilisome Degradation during Nitrogen Starvation in Synechococcus elongatus PCC 7942 - Lahmi, Roxane (American Society for Microbiology, 2006)
Degradation of the cyanobacterial light-harvesting antenna, the phycobilisome, is a general acclimation response that is observed under various stress conditions. In this study we identified a novel mutant of Synechococcus elongatus PCC 7942 that exhibits impaired phycobilisome degradation specifically during nitrogen starvation, unlike previously described mutants, which exhibit aberrant degradation under nitrogen, sulfur, and phosphorus starvation conditions. The phenotype of the new mutant, AldΩ, results from inactivation of ald (encoding alanine dehydrogenase). AldΩ is deficient in transcription induction of a number of genes during nitrogen starvation. These genes include the “general nutrient stress-related” genes, nblA and nblC, the products of which are essential for phycobilisome degradation. Furthermore, transcripts of several specific nitrogen-responsive genes accumulate at lower levels in AldΩ than in the wild-type strain. In contrast, ald inactivation did not decrease the accumulation of transcripts during sulfur starvation. Transcription of ald is induced upon nitrogen starvation, which is consistent with the ability of wild-type cells to maintain a low cellular content of alanine under these conditions. Unlike wild-type cells, AldΩ accumulates alanine upon nitrogen starvation. Our analyses suggest that alanine dehydrogenase activity is necessary for an adequate cellular response to nitrogen starvation. Decomposition of alanine may be required to provide a sufficient amount of ammonia. Furthermore, the accumulated alanine, or a related metabolite, may interfere with the cues that modulate acclimation during nitrogen starvation. Taken together, our results provide novel information regarding cellular responses to nitrogen starvation and suggest that mechanisms related to nitrogen-specific responses are involved in modulation of a general acclimation process.